Respuesta :

Answer:

82

Step-by-step explanation:

49 - 3 + 72/2

= 46 + 36

= 82

For this case we must find the value of the following expression:

[tex]7 ^ 2[/tex]-3 + 9 * 8÷2 =

According to the PEMDAS algebraic order of operations:

P: Perform any calculation within parentheses

E: Simplify any exponential expressions.

MD: Do all the multiplications and divisions, from left to right, as they appear.

AS: Do all the addition and subtraction, from left to right, as they appear.

So:

49-3 + 9 * 8÷2 =

49-3 + 72÷2 =

49-3 + 36 =

46 + 36 =

82

ANswer:

82

ACCESS MORE